Å leve i et minefelt - Gjertsen, Marit (Norway : Videomaker, 2006)
An Vi lives in Somloth, a small village in Cambodia. She has been the sole provider for her eight daughters since her husband passed away killed by a landmine - one of the many thousands of landmine victims in rural Cambodia. Poverty however, pushes An Vi to start cultivating a piece of land herself knowing that it is covered with landmines.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films